2017
DOI: 10.1016/j.aott.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Association between aspartic acid repeat polymorphism of the asporin gene and risk of knee osteoarthritis: A systematic review and meta-analysis

Abstract: ObjectiveStudies have assessed the association between aspartic acid (D)-repeat polymorphism in the gene encoding Asporin (ASPN) and knee osteoarthritis (KOA) risk, but the results were inconclusive and contradictory. Therefore, we performed a meta-analysis to investigate the association between ASPN gene D-repeat polymorphism and KOA risk.MethodsEligible studies were identified by searching several electronic databases for relevant reports published before September 2016. The pooled odds ratios (ORs) for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 33 publications
0
30
1
1
Order By: Relevance
“…After reading the full texts of the remaining 37 articles, we found one article had not sufficient data of genotype for calculating OR and 95% CI, four articles were meta-analyses, and two articles were reviews. Finally, a total of 30 studies (4)(5)(6)(7)(10)(11)(12)(13)(14)(16)(17)(18)(19)(20)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) published from 2002 and 2015 with 6,101 cases and 8,557 controls met our inclusion criteria. The main characteristics of these studies were listed in TABLE 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading the full texts of the remaining 37 articles, we found one article had not sufficient data of genotype for calculating OR and 95% CI, four articles were meta-analyses, and two articles were reviews. Finally, a total of 30 studies (4)(5)(6)(7)(10)(11)(12)(13)(14)(16)(17)(18)(19)(20)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) published from 2002 and 2015 with 6,101 cases and 8,557 controls met our inclusion criteria. The main characteristics of these studies were listed in TABLE 1.…”
Section: Resultsmentioning
confidence: 99%
“…The Q-statistic and the I 2 -statistic were used to assess the heterogeneity between studies in the meta-analysis. I 2 was a value describe the degree of heterogeneity between studies, where 0-25% indicated no observed heterogeneity and larger values showed increasing heterogeneity, with 25%-50% regarded as low, 50%-75% as moderate, and 75%-100% as high (18,19) . A P-value greater than 0.10 for the Q-statistic indicates a lack of heterogeneity between studies, so the pooled OR estimate of the included studies was calculated by the fixed-effects model (MantelHaenszel method) (20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery combined with adjuvant chemotherapy is currently the standard treatment for osteosarcoma (1). In recent years, although a great deal of effort has been made toward improving chemotherapy regimens, the overall prognosis remains poor and much of this may be attributed to drug resistance (2).…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is the most common malignant tumor of the bone and remains the second leading cause of cancer-associated mortality in adolescents globally at present (1). Surgery combined with adjuvant chemotherapy is currently the standard treatment for osteosarcoma (1).…”
Section: Introductionmentioning
confidence: 99%